THE ARCHITECTURE OF EU COMPANY LAW PROVISIONS PROTECTING WHO, WHAT AND HOW? - Mélon, Lela (European Scientific Journal, ESJ, 2015)
The stakeholder-oriented nature of EU company law can be observed in the case of public or private limited liability companies. In the case of the former, protection of shareholders also comes in the forefront and it can be found through the information model legislation, demanding all relevant information to be presented to the shareholders, on the basis of which the shareholders take on the responsibility for their decisions. This shift of responsibility for protection from legislative provisions in the hands of company law actors can be also observed in the case of provisions addressed to creditors , albeit in limited form. The interplay of the two legislative approaches - information based Anglo-American approach and (minimum) harmonization Continental approach can be seen throughout the body of EU company law, including CJEU case law, but the use of one or another does not always depend on the EU legislative policy. The lack of harmonization of some basic company law principles across the national laws of Member States contributes to these shifts of legislative approaches and it does not always coherently follow the aims and goals of EU legislature concerning the internal market and international competitiveness of European businesses. In particular, competitiveness that is based on comparative advantages and not merely on size is at the present moment not promoted at the EU level. A company that focuses on internal growth and decides to change its legal form to public limited liability company faces a vast shift in applicable EU company law provisions that entail high costs, not providing a visible initiative for businesses to undertake such path. A shift in policy considerations would be advisable to achieve the goal that arose in the last decades at the EU level: since internal market is today insured, international competitiveness is next on the agenda and the same policy considerations as they were provided in the 1950s cannot hold today in the changed circumstances.